SISTEM INFORMASI PEMBAYARAN IURAN SEKOLAH SISWAPADA SMK YAYASAN BAKTI PRABUMULIH DENGAN METODE WATERFALL - Suhartini suhartini; Yuntari Purbasari (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2020)
All studies aim to build a payment information system. The system was developed using NetBeans IDE 7.4, iReport-5.6.0, and XAMPP 1.7.3 software. This system works to be able to enter the transaction data of payment of tuition fees, such as monthly fee, uniform fee, registration fee and make payment report automatically. The purpose of this system is to facilitate staff or administrative personnel in conducting payment transactions dues. Effective monthly student fee system will trigger performance from agency to be better than before. For that required a system capable of handling the process of payment of student dues. By using the system of payment of contribution is expected to assist the performance of the agency. With the implementation of this system at Yayasan Bakti Vocational Technical School, can reduce errors of payment that may occur. This system can also speed up the process of payment and preparing reports that ultimately can help Yayasan Bakti Vocational Technical School.